Systematic reductions in differential ratings of perceived exertion across a 2-week repeated-sprint-training intervention that improved soccer players` high-speed-running abilities - McLaren, S. J.; Taylor, J. M.; Macpherson, T. W.; Spears, I. R.; Weston, M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To quantify changes in differential ratings of perceived exertion (dRPE) across a 2-wk repeated-sprint-training intervention that improved high-intensity intermittent-running ability and linear speed of semiprofessional soccer players. Methods: Thirteen players completed 3 (sessions 1-3) or 4 (sessions 4-6) sets of 7 sprints (group 1 [n = 7]: 30-m straight; group 2 [n = 6]: 2 × 10-m shuttle), with 20 s and 4 min of recovery between sprints and sets, respectively. Postset perceptions of breathlessness (RPE-B) and leg-muscle exertion (RPE-L) were rated using the CR100 scale. Results: Overall, RPE-B (mean [SD]: 46 [13] arbitrary units [AU], "hard") was most likely higher than RPE-L (39 [13] AU, "somewhat hard," mean difference: 8 AU; 90% confidence limits [CLs]: ±2). Set-to-set increases in dRPE (in AU; 90% CL: approximately ±2) were large in session 1 (RPE-B: 15; RPE-L: 14), moderate in sessions 2-5 (RPE-B: 7-10; RPE-L: 7-8), and small (RPE-B: 6) to moderate (RPE-L: 7) in session 6. Across the intervention, RPE-B reduced moderately in sets 3 (-13; 90% CL: ±4) and 4 (-12; 90% CL: ±12) and RPE-L reduced by a small magnitude in set 3 (-5; 90% CL: ±6). The set 4 change in RPE-L was unclear (-11; 90% CL: ±13). Conclusions: The authors observed systematic intrasession and intersession changes in dRPE across a 2-wk repeated-sprint-training intervention, with a fixed prescription of external load that improved semiprofessional soccer players` high-speed-running abilities. These findings could support dRPE as a measure of internal load and highlight its usefulness in evaluating repeated-sprint-training dose-response.